Doppler Assessment of Inferior Thyroid Artery and its Correlation with Thyroid Volume in Euthyroid Adults: A cross-sectional Study - Ghimire, Prasanna; Ghimire, Pragya Gautam (Nepal Journal of Medical Sciences, 2026)
Introduction: Doppler ultrasound provides hemodynamic information about thyroid vascularity. Establishing normative values for inferior thyroid artery parameters is essential for differentiating physiological from pathological conditions. This study aimed to determine normative Doppler parameters of the inferior thyroid artery in clinically euthyroid adults in Nepal. Methods: A cross-sectional study was conducted with 122 clinically euthyroid adults aged 18 years and above at a tertiary care hospital from January 1st to March 31st, 2024. Doppler parameters including Peak Systolic Velocity (PSV), Resistive Index (RI), and Pulsatility Index (PI) were measured using high-resolution ultrasound. Descriptive statistics, independent t-tests, one-way ANOVA, and Pearson correlation analyses were performed using SPSS version 25.0. Results: The mean PSV was 17.66 cm/s (SD ± 2.82), RI was 0.50 (SD ± 0.06), and PI was 0.72 (SD ± 0.08). Mean thyroid volume was 8.01 mL (SD ± 2.48) for the overall cohort, with males showing 8.20 mL (SD ± 2.95) and females 7.83 mL (SD ± 1.93). No significant gender differences were observed in PSV (p=0.41), RI (p=0.08), PI (p=0.18), or thyroid volume (p=0.52). Weak correlations were found between PSV and age (r=-0.15) and between Peak Systolic Velocity and thyroid volume (r= -0.02). Conclusions: This study provides baseline normative data for inferior thyroid artery Doppler parameters in euthyroid Nepali adults. The findings demonstrate stable hemodynamics across genders and age groups, serving as reference values for clinical practice